PENGARUH KEGIATAN SEKTOR INDUSTRI, PERTAMBANGAN DAN TRANSPORTASI TERHADAP KUALITAS LINGKUNGAN DITINJAU DARI EMISI CO2 DI INDONESIA - Ayudhia Andarini; Idris Idris; Ariusni Ariusni (Universitas Negeri Padang, 2016)
Carbondioxyde emission is kind of green house gases that has highestconcentration in he atmosphere than the ohers green house gases. The aim of thisresearch is that analyzing influence of industry sector, mining sector, and transportationsector avtivities to the environment quality base on the carbondioxyde emission inIndonesia. This analysis used regression model with Ordinary Least Square method(OLS). Result of analysis indicate that Gross Domestic Product (GDP) of industry sectorhas negative and significant influence to carbondioxyde emission in Indonesia, with significant value at 0.00, Gross Domestic Product (GDP) of mining sector has positiveand significant influence to carbondioxyde emission in Indonesia with significant value at0.00 and Gross Domestic Product (GDP) of transportation sector has positive andsignificant influence to Economic Growth in Indonesia, with significant value at 0.00.Then, Gross Domestic Product (GDP) of industry sector, mining sector andtransportation sector have significantly influence to Economic growth in Indonesia withsignificant value at 0.00 based on with the theory Environmental Kuznet Curve (EKC).